Accuracy of the pre-hospital triage tools (qSOFA, NEWS, and PRESEP) in predicting probable COVID-19 patients' outcomes transferred by Emergency Medical Services - Peyman Saberian; Nader Tavakoli; Parisa Hasani-Sharamin; Maryam Modabber; Mahnaz Jamshididana; Alireza Baratloo (Babol University of Medical Sciences, 2020)
Background: This study aimed to evaluate the efficiency of pre-hospital triage tools including the qSOFA, NEWS, and PRESEP in determining the prognosis of probable COVID-19 patients. Methods: In this diagnostic accuracy study, all probable COVID-19 patients older than 16-year-old who were transferred to the hospital by the Tehran Emergency Medical Services (EMS) during the first month of the pandemic, entered to the study. The scores of qSOFA, NEWS, and PRESEP were calculated using data gathered while providing pre-hospital care. The primary outcome was death; and the secondary outcomes were ICU admission, length of stay in the ICU, and length of hospital stay. Results: The data of 557 individuals with the mean age of 56.93±18.31 were analyzed of whom 67.5% were males. The area under the ROC curve (AUC) of qSOFA, NEWS, and PRESEP for ICU admission was 0.553, 0.557, and 0.551, respectively. The AUC of qSOFA, NEWS, and PRESEP for death was 0.596, 0.566, and 0.604, respectively. The best obtained cut-off point for qSOFA was a score >0 (the sensitivity and specificity were 25.0 and 85.68%, respectively), for NEWS was a score >2 (the sensitivity and specificity were 83.61 and 32.67%, respectively), and for PRESEP was a score >1 (the sensitivity and specificity were 54.10 and 55.56%, respectively). Conclusion: Based on the findings of the current study, it is likely that the available pre-hospital triage tools (qSOFA, NEWS, and PRESEP) do not have proper efficacy to predict death, ICU admission, and disease severity of COVID-19 patients.